(untitled) (Journal of the College of Basic Education, 2022)
This research deals in its contents with a study and analysis of the positions and opinions of the Iraqi National Assembly (MPs and notables) 1953-1958 regarding endowments, which is one of the important social issues during the time period of the research . The importance of the research lies in the fact that it deals with religious, social and cultural issues in Iraqi society during the reign of King Faisal II. In terms of knowing the negative and positive phenomena in the administration of endowments through the opinions and positions of the members of the National Assembly when proposing any issue related to the endowments, so our choice fell on this topic and the duration of the research was determined (1953-1958) as it represents the era of the last king of Iraq, Faisal II and the exercise of his constitutional duties. And it has been proven that the Iraqi National Assembly has placed the issue of endowments in an important place in many of the National Assembly sessions during the years 1953-1958, in which it dealt with many issues about endowments, and we can say that the observations and opinions of the National Assembly were in many cases similar, with regard to the demands for reform of endowments and attention In addition to the fact that it was objective and provided a solution to an important issue, its shortcomings were that it was reduced to members of the opposition to the government in the parliament more than the supporters, in addition to that it was limited to some brigades and not others.